Novel bovine-associated pVAPN plasmid type in Rhodococcus equi identified from lymph nodes of slaughtered cattle and lungs of people living with HIV/AIDS - Ribeiro, M. G. [UNESP]; Lara, G. H.B. [UNESP]; da Silva, P.; Franco, M. M.J. [UNESP]; de Mattos-Guaraldi, A. L.; de Vargas, A. P.C.; Sakate, R. I.; Pavan, F. R. [UNESP]; Colhado, B. S. [UNESP]; Portilho, F. V.R. [UNESP]; Motta, R. G.; Kakuda, T.; et al. (Hindawi, 2018)
Rhodococcus equi is a well-recognized Gram-positive intracellular facultative bacterium that is opportunistic in nature, which causes pyogranulomatous infections in humans and multiple host animals. The pathogenicity of the microorganism has been attributed to the presence of plasmid-encoded virulence-associated proteins (Vap). To date, three host-associated virulence plasmid types of R. equi have been identified as follows: the circular pVAPA and pVAPB, related, respectively, to equine and porcine isolates, and a recently described linear pVAPN plasmid associated with bovine strains, although these three types are found in human isolates. Recent phylogenomic studies support the evidence that human R. equi infection is zoonotically acquired. Nevertheless, data regarding distribution and prevalence of the host-adapted virulence plasmid types of R. equi isolated from meat animals are scarce or unnoticed. Here, the three host-associated virulence plasmid types (pVAPA, pVAPB, and pVAPN) were investigated in 154 R. equi isolates recovered from lymph nodes of cattle with lymphadenitis (n = 31), faeces of cattle without enteric signs (n = 49), as well as different clinical specimens from human patients (n = 74). The analysis of virulence profile of 74 R. equi from humans revealed six (8.1%) isolates pVAPB (type 8), two (2.7%) pVAPN, and one (1.3%) pVAPB (type 11), all of which were from lung samples from people living with HIV/AIDS. From the lymph node samples of cattle, 41.9% (13 of 31) isolates revealed pVAPN type, whereas all isolates from faecal samples were negative for three host-associated types. Here, recently described bovine-associated pVAPN type was detected in R. equi isolates recovered from the lungs of people living with HIV/AIDS and lymph nodes from slaughtered cattle intended for human consumption; a finding that represents a public health concern, mainly in countries where undercooked or raw meat are traditionally consumed.
Keywords: bovine rhodococcosis; emerging disease; host-associated plasmid types; immunocompromised human patients; pVAPN